North-Western Himalayan Common Beans: Population Structure and Mapping of Quantitative Anthracnose Resistance Through Genome Wide Association Study - Banoo, Aqleema; Nabi, Asha; Rasool, Rovidha S.; Mahiya-Farooq,; Shah, Mehraj D.; Ahmad, Mushtaq; Sofi, Parvaze A.; Aasiya-Nabi,; Itoo, Hamidullah; Sharma, P. N.; Padder, Bilal A. (Frontiers in Plant Science, 2020)
Common bean (Phaseolus vulgaris L.) is an important legume crop of north-western (NW) Himalayan region and the major disease that causes catastrophic loss to the crop is anthracnose, which is caused by Colletotrichum lindemuthianum. The pathogen is highly diverse and most of the commercial cultivars are susceptible to different races prevalent in the region. The lack of information on the genomic regions associated with anthracnose resistance in NW Himalayan common bean population prompted us to dissect Quantitative Resistance Loci (QRLs) against major anthracnose races. In this study, 188 common bean landraces collected from NW region were screened against five important anthracnose races and 113 bean genotypes showed resistance to one or multiple races. Genotyping by sequencing (GBS) was performed on a panel of 192 bean lines (4 controls plus 188 Indian beans) and 22,589 SNPs were obtained that are evenly distributed. Population structure analysis of 192 bean genotypes categorized 188 Indian beans into two major clusters representing Andean and Mesoamerican gene pools with obvious admixtures. Many QRLs associated with anthracnose resistance to Indian C. lindemuthianum virulences (race 3, 87, and 503) are located at Pv04 within the gene models that encode typical resistance gene signatures. The QRLs associated with race 73 are located on Pv08 and overlaps with Co-4 anthracnose resistance gene. A SNP located at distal end of Pv11 in a gene model Phvul.011G202300 which encodes a LRR with a typical NB-ARC domain showed association with race 73 resistance. Common bean genomic regions located at Pv03, Pv09, and Pv11 showed association with resistance to anthracnose race 2047. The present study showed presence of many novel bean genomic regions associated with anthracnose resistance. The presence of Co-4 and Co-2 genes in our material is encouraging for breeding durable anthracnose resistant cultivars for the region.